Strategi Guru Tahfidz dalam Meningkatkan Minat Menghafal Pada Santri Kelas VIII MTs Yayasan Islamic Centre Sumatera Utara - Teuku Adam Aliksan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the strategies applied by tahfidz teachers in increasing interest in memorization among 8th grade MTS students at the Islamic Centre Foundation of North Sumatra. In addition, this study also wants to identify the factors that support and hinder the strategy. The method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. The findings of this study indicate that one of the strategies used by tahfidz teachers to increase interest in memorization is by applying the tasmi' method. As for this research, there are supporting factors in increasing students' interest in memorizing, which consist of internal and external factors. Internal supporting factors come from oneself, namely the spirit of memorization and a strong will, besides that, external factors consist of the home and school environment, such as support from parents and motivation from teachers. As for the inhibiting factors for each student, most of the students themselves experience fatigue and often feel bored. In addition, teachers also conduct learning evaluations which are carried out every day